2019
DOI: 10.1158/1078-0432.ccr-18-1281
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factor Myeloid Zinc-Finger 1 Suppresses Human Gastric Carcinogenesis by Interacting with Metallothionein 2A

Abstract: Purpose: Metallothionein 2A (MT2A) suppresses the progression of human gastric cancer potentially through an "MT2A-NF-kB pathway" with unclear mechanisms. This study explored the role of a transcription factor, myeloid zinc-finger 1 (MZF1), in MT2A-NF-kB pathway and its clinical significance in gastric cancer. Experimental Design: MZF1 expression and function in gastric cancer were investigated in vitro and in vivo. The relationship between MZF1 and MT2A was determined by gain-offunction and loss-of-function a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
44
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 47 publications
6
44
1
Order By: Relevance
“…When metallothionein-2 was inhibited in the parent MSCs, the antiinflammatory effects of MSC-Exos on macrophages in vitro were significantly suppressed. NF-κB signaling is a downstream target of metallothionein-2 (27,43). Consistent with this, MSC-Exos induced a significant decrease in NF-κB activity, whereas this effect was compromised when the expression of metallothionein-2 in MSC-Exos was inhibited.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…When metallothionein-2 was inhibited in the parent MSCs, the antiinflammatory effects of MSC-Exos on macrophages in vitro were significantly suppressed. NF-κB signaling is a downstream target of metallothionein-2 (27,43). Consistent with this, MSC-Exos induced a significant decrease in NF-κB activity, whereas this effect was compromised when the expression of metallothionein-2 in MSC-Exos was inhibited.…”
Section: Discussionsupporting
confidence: 65%
“…As expected, the inhibitory effect of MSC-Exos on NF-κB activation was compromised as well ( Figure 8E). It has been reported that metallothionein-2 could enhance IκBα transcription via interacting with myeloid zinc finger 1 (MZF1), which directly bound to IκBα promoter (27). In agreement with this, MSC-Exos failed to enhance IκBα transcription in macrophages when MZF1 was knocked down using siRNA (Supplemental Figure 6E), implying a vital role of MZF1 on the increase of IκBα transcription.…”
Section: Effect Of Msc-exos On Mucosal Inflammation and Intestinal Basupporting
confidence: 73%
See 1 more Smart Citation
“…Besides, MZF1 might play key roles also in tumor microenvironment such as mesenchymal stem cell differentiation into cancer-associated fibroblasts [20]. However, MZF1 has also been shown to activate tumor suppressor genes such as FPN [41], NFKBIA [42], and SMAD4 [43]. In a more complex manner, MZF1 also plays a transcriptional repressor role for pro-tumorigenic genes such as MMP-2 [44] and IGF-IR [45].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the refractoriness to irinotecan and cisplatin may be due in part to MTs because (i) MTs have been found up-regulated in GAC, affecting the efficacy of cisplatin and irinotecan [51,52]; (ii) irinotecan induces MTs up-regulation promoting the development of chemoresistance in GAC patients [51]; (iii) the combination of MTs overexpression and p27 down-regulation seems to be related with poor prognosis of GAC patients [56]. In contrast, another study reported that GAC with a higher MT2A expression showed a better response to chemotherapy and prolonged survival [57,58]. Moreover, some studies revealed lower MTs expression in GAC than in the surrounding healthy tissue [59].…”
Section: Mechanisms Of Chemoresistance Type 2 (Moc-2)mentioning
confidence: 99%